Switching from oral risperidone to flexibly dosed oral paliperidone extended-release: core symptoms, satisfaction, and quality of life in patients with stable but symptomatic schizophrenia: the RISPALI study. (April 2014) - Gattaz, Wagner F.; Campos, João Alberto de Oliveira; Lacerda, Acioly L.T.; Henna, Elaine; Ruschel, Sandra Inês; Bressan, Rodrigo A.; de Oliveira, Irismar Reis; Rocha, Fábio Lopes; Grabowski, Hamilton M.; Sacomani, Ernindo; Louzã, Mario R.; Quevedo, João; et al.
<x xml:space="preserve">Abstract</x> Abstract Objective: The purpose of this prospective study was to evaluate the effects of switching from oral risperidone to flexibly dosed oral paliperidone extended-release (ER) in Brazilian adults with schizophrenia because of lack of efficacy, intolerability, or nonadherence after a minimum trial of 30 days on adequate (labeled) doses of oral risperidone, according to individual clinical judgment. Research design and methods: Subjects with Positive and Negative Syndrome Scale total scores above 78, and/or intolerable adverse effects, with risperidone received open-label paliperidone ER 3 to 12 mg daily for 26 (main phase) to 52 (extension phase) weeks. Clinical trial registration: Clinicaltrials.gov identifier: NCT01010776. Results: The intent-to-treat (efficacy) populations comprised 213 subjects in the main phase and 159 in the extension phase. Of 213 subjects with baseline and post-baseline efficacy data, 154 (72.3%) switched from risperidone to paliperidone ER because of a lack of efficacy and 59 (27.7%) because of tolerability issues, according to individual clinical judgment. Paliperidone ER significantly (p < 0.0500) improved a broad spectrum of efficacy endpoints from baseline, as early as the first post-baseline visit (Visit 2; 4 weeks) and persisting through 26 to 52 weeks. On most efficacy endpoints, function improved from baseline to the first post-baseline visit (week 4) and remained significantly improved compared to baseline at each visit for paliperidone ER treatment, at weeks 8, 13, 26, 39, 26, and 52; data are reported herein mainly for 26 and 52 weeks compared to baseline. Significant improvements from baseline were observed for the Positive and Negative Syndrome Scale total score and subscale scores (each p < 0.0001 at 26 and 52 weeks vs. baseline); and personal and social functioning (p < 0.0001 at 26 and 52 weeks). Paliperidone ER also significantly improved health-related quality of life (Short-Form 36) from baseline, particularly on the Mental Component Summary (p = 0.0011 at 26 weeks and p = 0.0019 at 52 weeks). Treatment with paliperidone ER also significantly improved (vs. baseline) sleep quality (according to decreases on the Pittsburgh Sleep Quality Index; p < 0.0001 at each visit vs. baseline) and disease severity (Clinical Global Impression–Severity; p < 0.0001 at each visit vs. baseline). Paliperidone ER was well tolerated. Adverse events occurring in at least 10% of subjects in either phase were insomnia (14.9% in the main phase and 8.8% in the extension phase); increased body weight (10.7% and 12.6%, respectively); and anxiety (10.7% and 2.5%). Most of these adverse events were: 1) rated as mild or moderate; 2) did not prompt interventions such as paliperidone ER dose adjustment or interruption; and 3) decreased in frequency from the main to the extension phase. Conclusions: Oral paliperidone ER is a rational treatment alternative for patients with schizophrenia whose antipsychotic regimens are switched because of unsuccessful treatment with oral risperidone according to individual clinical judgment. Study limitations included the open-label study design, lack of placebo, and use of subjective clinical judgment to determine lack of efficacy, intolerability, or nonadherence with oral risperidone.